Synthesis, Characterization and Magnetic Hyperthermia of Monodispersed Cobalt Ferrite Nanoparticles for Cancer Therapeutics - Mauricio A. Medina; Goldie Oza; A. Ángeles-Pascual; Marlene González M.; R. Antaño-López; A. Vera; L. Leija; Edilso Reguera; L. G. Arriaga; José Manuel Hernández Hernández; José Tapia Ramírez (Molecules, 2020)
Magnetic nanoparticles such as cobalt ferrite are investigated under clinical hyperthermia conditions for the treatment of cancer. Cobalt ferrite nanoparticles (CFNPs) synthesized by the thermal decomposition method, using nonionic surfactant Triton-X100, possess hydrophilic polyethylene oxide chains acting as reducing agents for the cobalt and iron precursors. The monodispersed nanoparticles were of 10 nm size, as confirmed by high-resolution transmission electron microscopy (HR-TEM). The X-ray diffraction patterns of CFNPs prove the existence of cubic spinel cobalt ferrites. Cs-corrected scanning transmission electron microscopy–high-angle annular dark-field imaging (STEM–HAADF) of CFNPs confirmed their multi-twinned crystallinity due to the presence of atomic columns and defects in the nanostructure. Magnetic measurements proved that the CFNPs possess reduced remnant magnetization (MR/MS) (0.86), which justifies cubic anisotropy in the system. Microwave-based hyperthermia studies performed at 2.45 GHz under clinical conditions in physiological saline increased the temperature of the CFNP samples due to the transformation of radiation energy to heat. The specific absorption rate of CFNPs in physiological saline was 68.28 W/g. Furthermore, when triple-negative breast cancer cells (TNBC) in the presence of increasing CFNP concentration (5 mg/mL to 40 mg/mL) were exposed to microwaves, the cell cytotoxicity was enhanced compared to CFNPs alone.